Hubungan Kandungan Fluorida pada Air Sumur Gali dan Kebiasaan Menggosok Gigi dengan Kejadian Karies Gigi Anak Usia 6 – 10 Tahun di Rt 5 Desa Waplau - Maryam Lihi; Syariefah H. Waliulu; Zulfikar Lating; Ilyas Ibrahim; Iswandi Fataruba; Ima Ima (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Dental caries is a health problem that can occur across all age groups, with children being particularly vulnerable. This study aimed to investigate the association between fluoride concentrations in dug well water and tooth-brushing practices with the incidence of dental caries among children aged 6–10 years in RT 5, Waplau Village. A quantitative approach with a cross-sectional design was applied. The study involved 64 respondents selected through purposive sampling. Data were analyzed using univariate and bivariate methods, supported by chi-square statistical testing. The results demonstrated a significant relationship between fluoride levels and dental caries (p = 0.013; p < 0.05). Additionally, tooth-brushing habits were significantly associated with the occurrence of dental caries in children (p = 0.001; p < 0.05). In summary, the fluoride content in the well water used by respondents was within acceptable limits, and tooth-brushing behavior contributed to the development of dental caries among children in RT 5, Waplau Village.